SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) GUNA MENENTUKAN PRODUK UNGGULAN DI KABUPATEN GUNUNGKIDUL - Fajar Budi Hartono; Hendro Joko Prasetyo (Universitas Islam Lamongan, 2019)
Gunungkidul has sufficient natural resources and human resources. Various industrial sectors in the Regency include mining, agriculture, plantations, crafts and fisheries. The potential has not all been able to develop according to expectations because local governments have not been able to determine the leading industrial sector. The government needs a system that can help determine the superior industrial sector. The method used is the Simple Additive Weighting (SAW) Method. This method is able to provide alternative choices by comparing one criterion with other criteria, by first giving weights to each criterion. The test results of the system that has been built determine the order of products that are used as a reference to increase revenue in the industrial sector. This result will determine the order of products that need to be studied and improved because they have been automatically selected by the system